A preorganized triarmed bis-triazolylpyridine-calix(4)arene with high affinity and selectivity for minor actinides for nuclear waste treatment - Baccelli, Davide; Stracke, Jonas; Gullo, Maria Chiara; Weßling, Patrik; Grivas, Symeon; Rispoli, Francesco; Volpi, Stefano; Mele, Andrea; Geist, Andreas; Panak, Petra; Sansone, Francesco; Sittel, Thomas; et al. (Chemical communications, 2025)
The incorporation of three terdentate 2,6-bis-triazolyl-pyridine units on a calix[4]arene gives a preorganized lipophilic ligand with enhanced efficiency in binding trivalent actinides over lanthanides. Combined time-resolved laser-induced fluorescence spectroscopy, and 1D and 1H-15N HMQC NMR investigations allowed to propose the structures of the complexes and to provide insights into the actinide selectivity.
Zuerst veröffentlicht: 13. August 2025
Gesehen am 16.01.2026
Im Titel ist die Zahl 4 eckig geklammert